EU B solutions and Cross border Institutional Trust - Medeiros, E.; Santamaria. J. T.; Guillermo-Ramirez. M. (Taller Internacional Arqueología y patrimonio(s) en la raya luso-andaluza: Cooperación y futuro de los territorios fronterizos, 2023)
Mutual trust is a pre-condition to start cross-border processes, and institutional trust is vital to forge a sound and effective cross-border cooperation. It is widely debated that the recent covidfencing process in Europe chipped away existing long and medium-term cross-border institutional ties, in most European borders, at least for some time. The fundamental point is that the sudden closing of national borders also revealed how important are effective and well-functioning cross-border institutions to direct the reopening of such borders into functional cross-border areas. To appreciate more in-depth the importance of cross-border institutional trust in post-pandemic times, this article analyses to what extent the EU b-solutions initiative contributes to reinforcing it along European cross-border regions. The analysis concluded that this EU initiative maximises the value of EU tools and instruments, effective multi-level engagement and other responses to foster institutional cooperation. However, only a few European cross-border regions have benefited the most from this institutional support by b-solutions: the Benelux, plus Germany and France, as well as the Iberian cross-border areas.